SBADR: stable and bandwidth aware dynamic routing protocol for mobile ad hoc network. Issue 3 (26th May 2020) - Sharma, Anupama; Bansal, Abhay; Rishiwal, Vinay
Abstract : Purpose: Quality communication is a big challenge in mobile ad hoc networks because of a restricted environment for mobile devices, bandwidth-constrained radio connections, random mobility of connected devices, etc. High-quality communication through wireless links mainly depends on available bandwidth, link stability, energy of nodes, etc. Many researchers proposed stability and link quality methods to improve these issues, but they still require optimization. This study aims to contribute towards better quality communication in temporarily formed networks. The authors propose the stable and bandwidth aware dynamic routing (SBADR) protocol with the aim to provide an efficient, stable path with sufficient bandwidth and enough energy hold nodes for all types of quality of service (QoS) data communication. Design/methodology/approach: The proposal made in this work used received signal strength from the media access control (MAC) layer to estimate the stability of the radio connection. The proposed path stability model combines the stability of the individual link to compute path stability. The amount of bandwidth available for communication at a specific time on a link is defined as the available link bandwidth that is understood as the maximum throughput of that link. Bandwidth as a QoS parameter ensures high-quality communication for every application in such a network. One other improvement, towards quality data transmission, is made by incorporating residual energies of communicating and receiving nodes in the calculation of available link bandwidth. Findings: Communication quality in mobile ad hoc network (MANET) does not depend on a single parameter such as bandwidth, energy, path stability, etc. To address and enhance quality communication, this paper focused on high impact factors, such as path stability, available link bandwidth and energy of nodes. The performance of SBADR is evaluated on the network simulator and compared with that of other routing protocols, i.e. route stability based QoS routing (RSQR), route stability based ad-hoc on-demand distance vector (RSAODV) and Ad-hoc on-demand distance vector (AODV). Experimental outcomes show that SBADR significantly enhanced network performance in terms of throughput, packet delivery ratio (PDR) and normalized control overhead (NCO). Performance shows that SBADR is suitable for any application of MANET having random and high mobility. Research limitations/implications: QoS in MANET is a challenging task. To achieve high-quality communication, the authors worked on multiple network parameters, i.e. path stability, available link bandwidth and energy of mobile nodes. The performance of the proposed routing protocol named SBADR is evaluated by a network simulator and compared with that of other routing protocols. Statistical analysis done on results proves significant enhancement in network performance. SBADR is suitable for applications of MANET having random and high mobility. It is also efficient for applications having a requirement of high throughput. Practical implications: SBADR shows a significant enhancement in received data bytes, which are 1, 709, 788 and 326 more in comparison of AODV, RSAODV and RSQR, respectively. PDR increased by 21.27%, 12.1%, 4.15%, and NCO decreased by 9.67%, 5.93%, 2.8% in comparison of AODV, RSAODV and RSQR, respectively. Social implications: Outcomes show SBADR will perform better with applications of MANET such as disaster recovery, city tours, university or hospital networks, etc. SBADR is suitable for every application of MANET having random and high mobility. Originality/value: This is to certify that the reported work in the paper entitled "SBADR: stable and bandwidth aware dynamic routing protocol for mobile ad hoc network" is an original one and has not been submitted for publication elsewhere. The authors further certify that proper citations to the previously reported work have been given and no data/tables/figures have been quoted verbatim from the other publications without giving due acknowledgment and without permission of the author(s).